Deposition and characterization of nanocomposite Cr-based coatings - Cheong, Jhun Yew. (2012)
Hard coatings have been applied onto the surfaces of different tools to improve their lifetime, performance and efficiency. For high-speed machining and other high temperature applications, thermal stability and oxidation resistance of the hard coatings are crucial. Currently, TiAlN coatings represent state-of-the-art coating in the tools coating industry by providing good surface wear protection under operation temperatures up to 800 ºC. In many cases, however, this is still insufficient to meet the application requirements. In sight of this, research work for developing better performing coatings for high temperature applications has been a hot research topic.